Sistem Informasi Pengolahan dan Pelayanan Pelanggan PT. PLN Wilayah Manado Berbasis Web - Cindy P. C. Munaiseche; Cipta Ramadhani; Laode Muhamad Tajidun (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2010)
Equitable distribution of electricity needs a framework of PT. PLN (Persero) Manado region in an effort to improve the quality of customer service. To improve the service developed a WEB based information system that supports the activities of PT. PLN. Information systems processing and customer service PT. WEB-based PLN was built to serve the customers and the general public in terms of obtaining information, applying for the installation of electrical, power changes and other information. Its use is intended for the public, especially our customers to communicate with PLN Region Manado. System development process begins with the stage of analysis then perform design, including process design and database design. The design process is done by using the Use Case Diagram. From the use case then transformed into the program modules for implementation. While the database design was done by the method of modeling an Entity Relationship Diagram (ER-Diagram). Implementation of this information system development using Dreamweaver MX, PHP as the interface system and uses MySQL as its database. Web server used is Apache and the browser using Mozilla Firefox for Web applications.